Pengaruh Substitusi Silase Ikan Rucah Dengan Persentase Yang Berbeda Pada Pakan Buatan Terhadap Efisiensi Pakan, Pertumbuhan Dan Kelulushidupan Benih Ikan Mas (Cyprinus carpio) - Erfanto, Feri; Hutabarat, Johanes; Arini, Endang (Journal of Aquaculture Management and Technology, 2013)
Problems arising in the cultivation of carp is carp feed prices are relatively expensive, requiring alternative materials in an effort to improve the nutrient content of feed goldfish and fisheries as well as to utilize the waste to be processed into fish silage research aims assess the effect of the addition of trash fish silage the artificial feed on protein efficiency ratio, the efficiency of feed utilization, relative growth rate and survival rate of carp seed. The method used in this research is the experimental method. The material used is a seed carp with an average individual weight of 0.9 to 1 g. Experimental design used was completely randomized design (CRD) with 4 treatments and each with three replications. Feed given 3 times a day ie at 07.00, 13.00, and 16.00. Treatment A, B, C, and D is applied artificial feed trash fish silage added with a dose of A (0%), B (5%), C (10%) and D (15%)%. The variables measured were EPP, PER, RGR and SR. EPP values for treatments A, B, C, and D, respectively, 22.77; 34.65; 29.84, and 24.68%. PER values for treatments A, B, C, and D, respectively, 1.01; 1.40; 1.16, and 0.79%. RGR values for treatments A, B, C, and D, respectively, 3.72; 5.02; 4.48, and 3.91% / day. SR values for all treatments A, B, C, and D is 100%. Water quality values for all the treatment that the water temperature 25-27oC, pH 6.9 to 7.5, DO 5-7mg / L, and ammonia 0.39-1mg / L. The results showed that a different dose of rumen silage has a highly different significant result (P 0.05) to SR carp juvenile.